Impact of Maternal Diabetes and Hypertension on Postoperative Outcomes in Neonates Undergoing Major Abdominal Surgery: A Retrospective Study - Reddy E, Mallikarjuna; Subramaniam, Suresh Kanna; Akita, Akita; Arvindraj R, Arvindraj R (Journal of Neonatal Surgery, 2025)
Objective: This study aimed to assess the impact of maternal Type 2 Diabetes Mellitus (T2DM) and Hypertensive Disorders of Pregnancy (HDP) on postoperative outcomes in neonates undergoing major abdominal surgery. Methods: We conducted a retrospective cohort study of neonates who underwent abdominal surgery for congenital gastrointestinal anomalies between January 2020 and December 2024 at a tertiary care center. Maternal medical history, neonatal demographics, surgical interventions, and postoperative outcomes were analyzed. The primary outcome was the incidence of postoperative complications within 30 days. Secondary outcomes included sepsis, duration of mechanical ventilation, length of hospital stay, and mortality. Statistical significance was set at p<0.05. Results: Out of 204 neonates included, 62 (30.4%) were born to mothers with T2DM and/or HDP. These neonates had a higher incidence of postoperative sepsis (45.2% vs. 26.8%, p=0.008), prolonged mechanical ventilation (>5 days) (38.7% vs. 22.3%, p=0.015), and hospital stay >15 days (56.5% vs. 35.7%, p=0.012). Multivariate logistic regression revealed maternal T2DM (aOR 2.25, 95% CI: 1.18–4.29) and HDP (aOR 1.89, 95% CI: 1.05–3.39) as independent predictors of adverse postoperative outcomes. Conclusion: Maternal diabetes and hypertension significantly increase the risk of postoperative complications in neonates undergoing abdominal surgery. Early identification and optimized management of maternal comorbidities may improve surgical outcomes.